2018
DOI: 10.1007/s11356-018-1655-5
|View full text |Cite
|
Sign up to set email alerts
|

Potential harmful elements in coal dust and human health risk assessment near the mining areas in Cherat, Pakistan

Abstract: This study was aimed to investigate the potential harmful element (PHE) concentrations in coal dust and evaluate the human risk assessment and health effects near coal mining areas. For this purpose, dust samples were collected near various coal mines in Cherat, Pakistan, and analyzed for the PHE concentrations. Determined PHE concentrations were evaluated for the health risk assessment. Results revealed that ingestion was the major pathway as compared to others for PHE exposure. Individual chronic daily intak… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
35
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 86 publications
(51 citation statements)
references
References 59 publications
1
35
2
Order By: Relevance
“…There have been a number of statements about Cr from coal mining 37 , 38 . Many studies have identified the enrichment of Cr in coal dust or fly ash in the coal mining area 39 , 40 . For example, it has been well documented that the Cr concentrations in leachates of fly ash in Sarigkiol basin 41 accounted for more than 96% of the total Cr.…”
Section: Resultsmentioning
confidence: 99%
“…There have been a number of statements about Cr from coal mining 37 , 38 . Many studies have identified the enrichment of Cr in coal dust or fly ash in the coal mining area 39 , 40 . For example, it has been well documented that the Cr concentrations in leachates of fly ash in Sarigkiol basin 41 accounted for more than 96% of the total Cr.…”
Section: Resultsmentioning
confidence: 99%
“…Fine particles also penetrate more deeply throughout the respiratory system and are more likely to result in adverse health effects (https://www.esrl.noaa.gov/gmd/about/ airquality.html; Csavina et al 2012a, b;Entwistle et al 2019 and references therein). In some situations, ingestion is the main pathway (Ishtiaq et al 2018). Mining operations are understood to have some of the highest concentrations of potential harmful contaminants derived through anthropogenic activities, along with the highest particulate emissions and the highest risk to both human and environmental health (Csavina et al 2012b;Meyer et al 2015).…”
Section: Insight 2-a Member Of Seghmentioning
confidence: 99%
“…As it is known from the literature, coal dust causes a number of diseases, among which we distinguish anthracosis and pneumoconiosis caused by rare-earth elements. Both these diseases are incurable and irreversible [8][9][10][11][12]. It is necessary to at least prevent a person from inhaling dust.…”
Section: Fig 1 Photographs Of Visible Pollution In the Urban Settlementioning
confidence: 99%